The missing girls and women of China, Hong Kong and Taiwan a sociological study of infanticide, forced prostitution, political imprisonment, "ghost brides," runaways, and thrownaways, 1900-2000s - Huang, Hua-Lun, 1962- (McFarland & Co., 2012)
"In the past century, tens of millions of women and girls have disappeared in China, Hong Kong, and Taiwan. This sociological study explores the institutional factors contributing to the phenomenon of missing females, develops a typology for these populations, and lays a foundation for social scientists to examine lost populations in the future"--Provided by publisher.